From rural to rural urban integration in China: Identifying new vision and key areas for post-2020 poverty reduction strategy - Chen, Kevin Z.; Wu, Guobao; He, Xiaojun; Bi, Jieying; Wang, Zimeiyi (International Food Policy Research Institute, 2019)
China's achievements in poverty reduction in the past 40 years were impressive. This study aims to study the characteristics and trends of urban and rural poverty in China; to sort the changes and challenges of the poverty alleviation policy; to analyze the domestic and international poverty circumstances, as well as new problems faced by China's poverty reduction. Based on the new challenges identified, the study identifies a need for a new vision of China's post-2020 poverty reduction, in accordance with international experience, and to provide a policy-making reference in formulating the new poverty reduction strategy during the post-2020 era.